2017
DOI: 10.1002/joc.5164
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability and synoptic characteristics of dust cases over southwestern Saudi Arabia

Abstract: ABSTRACT:The synoptic characteristics and statistical variability of seasonal dust over southwestern Saudi Arabia are studied for the period from 1979 to 2006 using the aerosol index (AI) from the Total Ozone Mapping Spectrometer (TOMS) satellite, dust observations from surface stations, and meteorological data from the National Center for Environmental Prediction and the National Center for Atmospheric Research (NCEP/NCAR) reanalysis data set.The seasonal AI distribution indicates that approximately 80% of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Remote sensing dust data for global absorbing aerosols over land and sea have been retrieved from Total Ozone Mapping Spectrometer (TOMS) instruments (Herman et al, 1997;Torres et al, 1998); these measurements are known as the aerosol index (AI), which represents the difference between the backscattered radiation measurements between 331 and 380 nm (Hsu et al, 1999). Generally, the value of the AI is proportional to the optical depth and dust altitude (Mahowald et al, 2003), but dust near the surface produces a deficiency in the AI values, which can be overcome by using the threshold values (Prospero et al, 2002;Washington et al, 2003;Gao and Washington, 2009;Mashat et al, 2018). The AI data are daily data from the period from November 1978 to 2010, with a data gap from May 1993 to July 1996, and these data have a spatial resolution of 1.25 x 1.0 , where the data from 2007 to 2010 have been interpolated from the original resolution of 1.0 x 1.0 into 1.25 x 1.0 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing dust data for global absorbing aerosols over land and sea have been retrieved from Total Ozone Mapping Spectrometer (TOMS) instruments (Herman et al, 1997;Torres et al, 1998); these measurements are known as the aerosol index (AI), which represents the difference between the backscattered radiation measurements between 331 and 380 nm (Hsu et al, 1999). Generally, the value of the AI is proportional to the optical depth and dust altitude (Mahowald et al, 2003), but dust near the surface produces a deficiency in the AI values, which can be overcome by using the threshold values (Prospero et al, 2002;Washington et al, 2003;Gao and Washington, 2009;Mashat et al, 2018). The AI data are daily data from the period from November 1978 to 2010, with a data gap from May 1993 to July 1996, and these data have a spatial resolution of 1.25 x 1.0 , where the data from 2007 to 2010 have been interpolated from the original resolution of 1.0 x 1.0 into 1.25 x 1.0 .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used a combination of surface observations, remote sensing, and meteorological data collected over a long period—from 1978 to 2010—to study the variability, temporal and synoptic characteristics of the annual dust over northern Saudi Arabia, rather than that of individual seasons, as was performed in previous studies (e.g., Awad and Mashat, ; Awad et al ., ; Awad and Mashat, ). Another advantage of this study is that the cases for the climate synoptic study were selected from wide surface‐observed dust storms, that is, cases where at least three stations observed the dust storms (not conditional selections from remote sensing data, such as in Mashat et al ., ) and where the composite cases of climatology can be interpreted using remote sensing data. Therefore, this study provides clear examples of the seasonal synoptic features associated with dust storms over a region specified as a dust region climate over the Arabian Peninsula (Middleton, ) that is affected by its own dust (Hamidi et al ., ) and transported dust (Awad and Mashat, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, climate change might also have an impact on the frequency of dust storms, as drier and hotter conditions may reduce the overall vegetation coverage and, therefore, intensify the desertification process [38,78]. This is particularly important, as recent studies showed that long-term drought conditions linked to synoptic weather conditions (i.e., the configuration of high-pressure and low-pressure systems) control dust storm activities over large areas (e.g., [22,23,79]). This underlines the urgent need for future research investigating the spatio-temporal trends of dust storms across the Arabian Peninsula taking into account large-scale influencing factors such as land-use change and climate change.…”
Section: Large-scale Trends and Driversmentioning
confidence: 99%
“…Moreover, the Sudan low and the associated RST play an important role in the generation of the synoptic systems of the southern Mediterranean (Almazroui and Awad, ) or affect the daily synoptic systems in the EM region (Alpert et al, ). In addition, the RST influenced the development of the widespread dust over the northern Arabian Peninsula (Mashat and Awad, ) or the southwestern Arabian Peninsula (Mashat et al, ) when a high‐pressure gradient formed over and along the western part of the Arabian Peninsula between the RST and the Arabian Peninsula high pressure (Jish Prakash et al, ). Furthermore, Papadopoulos et al () show that in winter, the joint of Mediterranean low pressure and RST, which was defined in their work as the north extension of the Equatorial African low, induced a positive turbulent flux over the northern Red Sea region, whereas a negative turbulent flux was produced when the RST was located to the south.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated the importance of the RST extension/shrinking (e.g., Krichak et al, ; Tsvieli and Zangvil, ; de Vri es et a l. ( & ); Papadopoulos et al, ; Haggag and El‐Badry, ) or west–east orientation around the Red Sea (e.g., Tsvieli and Zangvil, , ) on the atmospheric systems and described the effects of weather characteristics of the RST in the Red Sea region. Nevertheless, most RST studies are either case studies (e.g., Haggag and El‐Badry, ; Mashat and Awad, ) or undertaken for short periods of time for specific purposes (e.g., Tsvieli and Zangvil, ; Mashat et al, ) and do not provide deep insights on the synoptic and climate characteristics of the RST and their seasonal variabilities. In addition, those studies do not discuss details or provide specific answers about the synoptic forces that controlled the RST extension–northward/southward shrinking, west–east orientation around the Red Sea and do not quantify the increasing/decreasing RST.…”
Section: Introductionmentioning
confidence: 99%